If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4y-6y+23=5y+20-3y
We move all terms to the left:
4y-6y+23-(5y+20-3y)=0
We add all the numbers together, and all the variables
4y-6y-(2y+20)+23=0
We add all the numbers together, and all the variables
-2y-(2y+20)+23=0
We get rid of parentheses
-2y-2y-20+23=0
We add all the numbers together, and all the variables
-4y+3=0
We move all terms containing y to the left, all other terms to the right
-4y=-3
y=-3/-4
y=3/4
| 3y-9y+y+43=6y+40-4y | | 4y-28=-34+y | | 7xx+2=40 | | 2n-10=18+n | | (x/15)(100)=125 | | a^2-16=81 | | s^2-16=81 | | s@-16=81 | | 4x+13=55 | | (2.0x-1.1)/5=0.5 | | 5x^2+28x=-1 | | (6-x)/2=2 | | 15x+4=18x-8 | | 50-u=187 | | x^2=(9/16) | | 6x+5=3x×14 | | (y-1/y-7)+1=y-4/y-3 | | 8+(x)/3=15 | | x^=9/16 | | 15x-6=10x-12 | | (x)/9=8 | | 28x-12=63x+28 | | 124=164–20j | | 6x-3=4x-12 | | 12x-5=-30x-12 | | 8/18=36/n | | 30*2x=40 | | 30x2x=40 | | 2u-10+4u+9=38 | | 2x-3=8x-6 | | -16t^2+24t-18=0 | | 12x+4=3x+24 |